2015
DOI: 10.1007/s00425-015-2256-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of phenolic biostimulants isolated from brown seaweed Ecklonia maxima on plant growth and development

Abstract: Eckol, a major phenolic compound isolated from brown seaweed significantly enhanced the bulb size and bioactive compounds in greenhouse-grown Eucomis autumnalis. We investigated the effect of eckol and phloroglucinol (PG) (phenolic compounds) isolated from the brown seaweed, Ecklonia maxima (Osbeck) Papenfuss on the growth, phytochemical and auxin content in Eucomis autumnalis (Mill.) Chitt. The model plant is a popular medicinal species with increasing conservation concern. Eckol and PG were tested at 10(-5),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Eckol a derivative of phloroglucinol might have a similar effect of auxin synergism to improve overall plant growth. Recently, in an in vitro experiment, eckol significantly improved endogenous indole acetic acid (IAA) levels in the medicinal plant Eucomis autumnalis [26]. Proline is a key protein organic amino acid essential for plant primary metabolism, which accumulates during various biotic and abiotic stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Eckol a derivative of phloroglucinol might have a similar effect of auxin synergism to improve overall plant growth. Recently, in an in vitro experiment, eckol significantly improved endogenous indole acetic acid (IAA) levels in the medicinal plant Eucomis autumnalis [26]. Proline is a key protein organic amino acid essential for plant primary metabolism, which accumulates during various biotic and abiotic stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of plants with eckol also had a positive effect on the flavonoid content, increasing the amount of kempferol in plants several times. However, foliar application of Kelpak increased the content of kaempferol in tubers and entire plants, as well as taxifolin in leaves of Eucomis autumnalis [85,115]. Increasing the content of bioactive compounds in plants treated with biostimulants is associated with a mechanism that includes the stimulation of the chalcone isomerase enzyme, involved in the biosynthesis of flavanone precursors [117].…”
Section: Discussionmentioning
confidence: 99%
“…Eckol (phenolic compound) found in seaweed extracts affects the phenylpropanoid pathway in the biochemical synthesis of phenolic acids [114]. Aremu et al [85,115] showed that the timing of eckol plants increases the content of phenolic compounds, such as p-hydroxybenzoic and ferulic acids. In turn, the Kelpak application increases the content of caffeic acid, ferulic acid [85,116], protocatechuic acid, p-hydroxybenzoic acid, gentisic acid, p-coumaric acid, and trans-cinnamic acid in Eucomis autumnalis [85]; however, the content of phenolic compounds depended on the biostimulant concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson and Van Staden [119] prove that some of the phenolic acids that protect auxins before decarboxilation increase the concentration of active forms of auxins, which are indispensable for the stimulation of growth and development of crop roots. However, according to Arem et al, attempts to explain mechanisms that are responsible for a positive response of plants to application of extracts from seaweeds should take into account the possible cross reactions between phytohormones included therein and the quantitative concentration of auxins, which may justify the observed morphological differences [120].…”
Section: Discussionmentioning
confidence: 99%
“…It also works as an index of somatic embryogenesis [121][122][123][124]. According to Aremu et al, a higher activity of esterase in plants that were treated with seaweed extracts indicated their stimulating impact on the increase of plant biomass production [120].…”
Section: Discussionmentioning
confidence: 99%